2012
DOI: 10.1002/asi.22676
|View full text |Cite
|
Sign up to set email alerts
|

Information sharing and trust during major incidents: Findings from the oil industry

Abstract: Communication and information sharing during the response to a major incident on oil rigs have been identified as significantly influencing capability to control, manage, and limit the effect of the incident. This article reports on one of the few studies of information sharing during such incidents. Interviews drawing on the critical incident technique were conducted with offshore emergency responders and supplemented by internal organizational reports and observations of emergency response exercises. We prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…Researchers suggest that respect for autonomy and appropriate exercise of authority help build up trust between participating organizations in CBIS initiatives [55]. Interestingly, in studying a major incident on oil rigs, Hassan Ibrahim and Allen [56] observe a counterintuitive relationship between trust and information sharing. They argue that better information sharing also plays a crucial role in instilling or enhancing trust among event participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers suggest that respect for autonomy and appropriate exercise of authority help build up trust between participating organizations in CBIS initiatives [55]. Interestingly, in studying a major incident on oil rigs, Hassan Ibrahim and Allen [56] observe a counterintuitive relationship between trust and information sharing. They argue that better information sharing also plays a crucial role in instilling or enhancing trust among event participants.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Rather than confine themselves within limited groups, some researchers have set out to study information behavior among minority or marginal groups such as pregnant women (for example, Laferriere and Crighton, 2017) and immigrants (for example, Lloyd et al, 2013). Alongside such work, numerous researchers have conducted relevant work in the context of the natural environment, including the home (for example, Foss et al, 2013) and workplace (for example, Hassan Ibrahim and Allen, 2012). The amount of information behavior research in the field of health and medicine in particular increased in the time spans researched (Eungi, 2017; Kim and Syn, 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Researchers also have studied the impact of shared information from different perspectives. For example, Hassan Ibrahim and Allen () examined the relationships between trust and information sharing in their study of communication and information sharing in a major incident from the oil industry. O'Connor () found that shared information could compromise investors' decision‐making processes in an analysis of information sharing and use in three investment discussion forums.…”
Section: Related Workmentioning
confidence: 99%